Oscillating pressure storage and gas exchange in apple fruit - Calbo, Adonai Gimenes; Sommer, Noel F. (Pesquisa Agropecuaria Brasileira, 2014)
An oscillating pressure storage system that is adapted to fruits and vegetables having low mass air flow resistance, is proposed. Periodic variations in air pressure induces high rates of gas exchange and reduces the internal level of ethylene. Apple (Malus domestica Borkh) fruit was used as the model commodity because it has a large intercellular volume and low mass air flow resistance. Frequency of 1 cycle/min and maximum pressure (Pi) to minimum pressure (Pf) reduction ratios [(Pi - Pf)/Pi)] 0.22 and 0.34, were tested in two storage trials. Oscillating pressure storage extended the preclimacteric life and decreased the rate of ethylene evolution from 'Gravenstein' and 'Granny Smith' apple. The pressure reduction ratio of 0.34 was more effective than 0.22. The effects of elevated CO2 and oscillating pressure were additive. The potentiality of oscillating pressure as a substitute for the hypobaric storage is discussed.
Keywords: Malus domestica; controlled atmosphere; hypobaric storage